The effect of rinsing and storage period in low temperature on the quality of scad fish sausage (Decapterus sp.) fortified with Moringa leaves (Moringa olifera) - Sahnita, Dewi; Suwetja, I Ketut; Onibala, Hens (Universitas Sam Ratulangi, 2013)
A research on sausage scad fish (Decapterus sp) using 4 treatments with 3 replications with complete randomized design. Washing is done 0 to 3 times and storage for 0 to 9 days. The results of the study addressed the interaction of storage time washing meat and kite fish sausage (Decapterus sp) are fortified with Moringa leaves an effect on levels of protein, fat and water content. Organoleptic quality sausages from the value in 9 days can still be accepted by the panelists. During storage protein value reduction from 0 days (16.38%) decreased (14.40%) on day 9. The water content increased from 0 days up to 61.22% 66.96% on day 9. Fat in fish sausage 0.64% down 0.19% on day 9. Good quality sausage was taken 9 days because of the old fish sausage stored beyond 9 days is not liked by the panelists, because the texture and taste was not goodÂ©Â Penelitian pembuatan sosis ikan layang (Decapterus sp) menggunakan 4 perlakuan dengan 3 kali ulangan dengan metode rancangan acak lengkap (RAL). Pencucian dilakukan 0 sampai 3 kali dan penyimpanan selama 0 sampai 9 hari. Hasil penelitian menunjukan bahwa interaksi pencucian daging dan lama penyimpanan sosis ikan layang (Decapterus sp) yang difortifikasi dengan daun kelor berpengaruh terhadap kadar protein, lemak dan kadar air. Mutu sosis dari nilai organoleptik dalam 9 hari masih bisa diterima oleh panelis. Selama penyimpanan nilai protein terjadi penurunan dari 0 hari (16,38%) menurun (14,40%) pada hari ke-9. Kadar air mengalami kenaikan dari 0 hari 61,22 % naik menjadi 66,96% pada hari ke-9. Lemak pada sosis ikan 0,64 % turun 0,19% pada hari ke-9. Sosis yang baik mutunya adalah dibawa 9 hari karena sosis ikan yang lama penyimpanannya melebihi dari 9 hari sudah tidak disukai oleh panelis, karena tekstur dan rasa sudah kurang baikÂ©